Análise de metilação do gene FOXE1 em carcinoma de células escamosas em cães: padronização metodológica - Pardini, Luciana Moura Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
It is believed that epigenetic mechanisms such as DNA methylation are important for the tumorigenesis and maintenance of the altered state of tumor cells. DNA methylation occurs by the addition of a methyl group to carbon 5 of cytosine, catalyzed by the enzyme DNA methyl-transferase, which can change the expression of a gene, including the tumor suppressor genes. In human squamous cell carcinoma, several features have shown the etiological role of genes in tumor development. Among them, FOXE1 gene (forkhead box E1 - thyroid transcription factor) is presented with an important role in susceptibility to disease. Similarly the FOXE1 methylation pattern could alter the expression of this gene in dogs and predisposed to tumor on. Therefore, this study aims to investigate in dogs, the validity of the strategy employed in humans to analyze the FOXE1 methylation status. DNA extraction from fresh frozen tumoral samples was performed by Wizard Genomic® DNA Purification Kit. The methylation status was determined by MSP-PCR (methylation-specific polymerase chain reaction), using 2.0 ng of DNA treated with sodium bisulphate. One hundred micrograms of bisulphite-modified DNA was amplified using primers specific for either methylated or unmethylated DNA (primers sequences are available at http://pathology2.jhu.edu/pancreas/primer.pdf). The analysis of fragments was loaded on to 7% polyacrylamide gels and silver nitrate staining. In this stage of technical approach, 60% were FOXE1 hypermethylated. In conclusion, it was observed that the standard technique for assessing the methylation pattern of gene FOXE1 in humans can be used for the same evaluation in dogs. The correlation of these molecular data with clinical and histopathological parameters may have diagnostic and prognostic value and still be used as a tumor marker for therapeutic decision and surgical approach

Acredita-se que mecanismos epigenéticos, como a metilação do DNA, são importantes para a iniciação da tumorigênese e a manutenção do estado alterado das células tumorais. A metilação no DNA ocorre pela adição de um grupo metil ao carbono 5 da citosina, reação catalisada pela enzima DNA metiltransferase, que pode alterar a expressão de um gene, entre eles os genes supressores de tumor. No carcinoma cutâneo de células escamosas em humanos, várias características têm evidenciado o papel etiológico de genes no desenvolvimento do tumor. Dentre eles, o gene FOXE1 (forkhead box E1 - thyroid transcription factor) apresenta-se com importante papel na suscetibilidade à doença. De maneira análoga, padrões de metilação em FOXE1 em cães podem alterar a expressão desse gene e predispor ao aparecimento do tumor. Sendo assim, o presente estudo tem por objetivos investigar em cães a validade da estratégia molecular empregada em humanos para análise do status de metilação do gene FOXE1. Foi realizada a extração de DNA de amostras tumorais frescas congeladas pelo Wizard Genomic® DNA Purification Kit. O status de metilação foi determinado pelo MSP-PCR (Reação em Cadeia da Polimerase Metilação-específica) com 2,0 ng de DNA tratado com bissulfito de sódio. Cem microgramas de DNA modificado por bissulfito foram amplificados, utilizando primers específicos para DNA metilado e nãometilado (sequência de primers disponível em http://pathology2.jhu.edu/pancreas/primer.pdf). A análise dos fragmentos foi realizada utilizando géis de poliacrilamida 7%, corados com nitrato de prata. Nos casos analisados nesta etapa de padronização técnica, 60% apresentaram hipermetilação para o gene FOXE1. Em conclusão, observou-se que a técnica para avaliar o padrão de metilação do gene FOXE1 em seres humanos pode ser utilizada para a mesma avaliação em cães... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Cão – Doenças; Carcinoma de celulas escamosas